COMPARATIVE EVALUATION OF ACCURACY OF RECORDING BLOOD PRESSURE EITHER BY AUTOMATED OSCILLOMETRIC METHOD OR BY SPHYGMOMANOMETER IN BOTH NORMOTENSIVE AND HYPERTENSIVE PATIENTS - A PROSPECTIVE OBSERVATIONAL STUDY - R, Sobana; S, Parthasarathy (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objectives: Automatic devices based on oscillometric principle are widely used for the estimation of blood pressure (BP). Mercury sphygmomanometer mean systolic BP (MSBP) and its derived cuff pressure are the traditional mode of estimation which is a validated and authenticated procedure. Automated machines using oscillometric method are slowly replacing the conventional technique. This study was done to compare the BP recorded by the mercury sphygmomanometer MSBP and the automated technique using oscillometric method automated office BP (AOBP). Methods: Two hundred subjects aged 40â€“65 years with mid-arm circumference 27â€“34 cm were recruited. MSBP and AOBP were recorded adhering to guidelines given by the American Heart Association Joint National Committee. The subjects were divided into two groups as normotensive (Group 1) and hypertensive (Group 2), and statistical analysis was performed. Results: The mean systolic and diastolic pressures estimated by oscillometric method and sphygmomanometer were calculated and compared with each other by paired t-test separately for Groups 1 and 2. In mormotensives (Group 1), the mean systolic pressure MSBP was 114.21Â±7.5 mmHg and AOBP was 118.24Â±11.0 mmHg. The mean diastolic MSBP was 72.1Â±3.5 mmHg and AOBP was 76.4Â±1.2 mmHg. Subjects of Group 2 (hypertensive) showed mean systolic pressure MSBP of 144.42Â±18.5 mm Hg and AOBP of 159.74Â±22 mmHg. The mean diastolic MSBP was 87.2Â±9.5 mmHg and AOBP was 96.9Â±9.2 mmHg. In Group 1, the difference was statistically not significant, while in Group 2, comparison by paired t-test showed a mean difference of systolic pressure by 15.32Â±1.25 (p<0.005), and mean difference of diastolic pressure by 8.9Â±5.8 (p<0.005). Conclusion: Hence, we conclude that oscillometric pressure recordings by the automated device are closer to manual measurements in normotensives but showed a significant high value in hypertensives. We suggest caution in treating hypertensives with values derived from automated machines only.